2006
DOI: 10.1111/j.1525-1497.2006.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants vitamin C and vitamin E for the prevention and treatment of cancer

Abstract: OBJECTIVE:To evaluate the evidence of the supplements vitamin C and vitamin E for treatment and prevention of cancer.METHODS: Systematic review of trials and meta-analysis. DATA SOURCES AND MAIN RESULTS:Thirty-eight studies showed scant evidence that vitamin C or vitamin E beneficially affects survival. In the ATBC Cancer Prevention Study Group, no statistically significant effect of treatment was seen for any cancer individually, and our pooled relative risk (regardless of tumor type) for a-tocopherol alone w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
2
6

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(83 citation statements)
references
References 43 publications
2
73
2
6
Order By: Relevance
“…A phase III clinical trial using megadoses of several vitamins including E, when compared to patients who just received the recommended daily allowance (RDA) of the same vitamins, had a 40% reduction in bladder tumor recurrence after the first 10 months of the study (Lamm et al, 1994). However, in this same study, patients also received BCG therapy, which is known to promote immune response to tumors and may have confounded the results (Coulter et al, 2006). Further support comes from a prospective study, which showed an inverse relationship between vitamin E supplement consumption and the risk of bladder malignancy in men (Michaud et al, 2000).…”
Section: Vitamin Ementioning
confidence: 87%
See 1 more Smart Citation
“…A phase III clinical trial using megadoses of several vitamins including E, when compared to patients who just received the recommended daily allowance (RDA) of the same vitamins, had a 40% reduction in bladder tumor recurrence after the first 10 months of the study (Lamm et al, 1994). However, in this same study, patients also received BCG therapy, which is known to promote immune response to tumors and may have confounded the results (Coulter et al, 2006). Further support comes from a prospective study, which showed an inverse relationship between vitamin E supplement consumption and the risk of bladder malignancy in men (Michaud et al, 2000).…”
Section: Vitamin Ementioning
confidence: 87%
“…In contrast to studies supporting vitamin E, a recent cohort study suggested no association of vitamin E intake and risk of urothelial carcinoma (Roswall et al, 2009). In addition, a meta-analysis for vitamin E and C intake and prevention of cancer indicated overall poor evidence for vitamin E in reduction of bladder cancer recurrence (Coulter et al, 2006). Additionally, a recently published cohort study indicated that the use of a variety of vitamins and supplements including vitamin E had no significant association with urothelial carcinoma risk in age-adjusted or multi-variate models (Hotaling et al, 2011).…”
Section: Vitamin Ementioning
confidence: 99%
“…However, other studies have shown that low-dose antioxidant supplementation is associated with reduced cancer incidence and all-cause mortality in men (76) , and supplemental b-carotene and vitamin E is associated with reduced risk of prostate cancer (77) . Two systematic reviews have found no evidence of benefit for antioxidant supplements in the prevention of cancer (78) .…”
Section: Antioxidantsmentioning
confidence: 99%
“…Effectiveness based on trial evidence Potentially-serious side effects Potentially-significant drug interactions Se Potentially effective for the prevention of gastrointestinal cancers (73) Clinical trials for prostate cancer ongoing (SELECT Trial) (12) Potential slight › in squamous and non-melanoma skin cancer risk at a dose of 200 mg daily (81) Acute toxicity: nausea causes vomiting, nail changes, irritability and weight loss; chronic toxicity resembles As toxicity (82) Chemotherapy Modification of chemotherapies relying on oxidative stress including taxols, anthracycline antibiotics, 5-fluorouracil, Pt agents, irinotecan (89)(90)(91) Unclear whether Se only reduces toxicity and improves therapeutic index of the respective chemotherapies or may affect long-term prognosis by reducing chemotherapy effectiveness (11) May › cetuximab efficacy in metastatic colorectal cancer (92) Other Potential fl effect of statins, › effect of anticoagulants including warfarin (82) May exacerbate hypothyroidism in patients with I-deficient hypothyroidism (93) Vitamin A Resolution of oral leukoplakia (74) No effect on the prevention of gastrointestinal cancers (73) › Mortality, statistically significant (43) Acute toxicity leads to neuro-psychiatric symptoms including delirium and coma (83) Hepatotoxicity (84,85) Hypervitaminosis leads to skin, bone and nail abnormalities (86) Benign intracranial hypertension (87,88) fl Bone density and › risk of hip fracture with long-term dietary intake (45) Other hepatotoxic drugs, including alcohol: › liver toxicity (85) Retinoids: › overall toxicity (83) Tetracyclines: › benign intracranial hypertension (87) Warfarin: › in bleeding risk through vitamin K antagonism (83) Vitamin C Possibly no benefit for prevention and treatment (75) No effect on the prevention of gastrointestinal cancers (73) Potential fl in breast-cancer risk (76) Effect on mortality unclear (43) Potential kidney damage through oxalate formation …”
Section: Supplementmentioning
confidence: 99%